2018
DOI: 10.4317/jced.54756
|View full text |Cite
|
Sign up to set email alerts
|

Intensity output and effectiveness of light curing units in dental offices

Abstract: BackgroundThe aims of the study were measuring the light intensity of light curing units used in Qazvin’s dental offices, determining the relationship between the clinical age of these units and their light intensity, and identifying the reasons for repairing them.Material and MethodsIn this cross-sectional study, the output intensity of 95 light curing devices was evaluated using a radiometer. The average output intensity was divided up into four categories (less than 200, 200-299, 300-500, and more than 500 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 11 publications
2
17
1
8
Order By: Relevance
“…On the other hand, the distribution of QTH in the present study was minimal at 11.5%, which is again similar to the field study analysis in Switzerland, showing 32.9% QTH units, 35 and the study by Omidi et al. showing 35.8% QTH units 31 …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…On the other hand, the distribution of QTH in the present study was minimal at 11.5%, which is again similar to the field study analysis in Switzerland, showing 32.9% QTH units, 35 and the study by Omidi et al. showing 35.8% QTH units 31 …”
Section: Discussionsupporting
confidence: 91%
“…This high distribution of LED units is in harmony with the field study analysis of Switzerland, which showed a 67.10% distribution for LED lights, 35 and the same trend was reported by a recent study by Omidi et al. in private dental practices, with a 64.2% prevalence of LED units 31 …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The use of budget priced LCUs that have often been purchased over the Internet is becoming popular 16 . Many of these budget LCUs appear to be equivalent to higher cost LCUs from quality manufacturers because these budget lights often claim similar radiant exitance (irradiance) values.…”
Section: Describing the Light-curing Unitmentioning
confidence: 99%
“…In the 80 s, studies had been conducted to assess the ocular hazards of quartz-tungsten halogen (QTH) LCUs and it was found that due to their low emission intensities of around 300 mW/cm 2 , they had little potential to cause ocular damage (Rueggebergf et al, 2017, Satromi et al, 1987, Al-Samadani et al, 2013). However, the plasma arc and LED curing units today have a very different spectra emission and emit irradiances of up to 3000 mW/cm 2 or more (Omidi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%